Full swing logic inverter with amorphous SiInZnO and GaInZnO thin film transistors - Debnath, Pulak Chandra; Lee, Sang Yeol (AMER INST PHYSICS, 2012)
A high-performance n-channel metal-oxide-semiconductor inverter implemented consisting of enhancement mode driving thin-film transistor with amorphous Ga-In-Zn-O (a-GIZO) and depletion mode load with amorphous Si-In-Zn-O (a-SIZO) is demonstrated. The threshold voltage of the post-annealed a-SIZO load thin film transistor (TFT) exhibits negative value while the threshold voltage of the GIZO driving TFT exhibits positive value. The proposed inverter composed of a-SIZO and a-GIZO TFT shows much improved switching characteristics with higher voltage gain. (C) 2012 American Institute of Physics. [http://dx.doi.org/10.1063/1.4747800]
Keywords: OXIDE SEMICONDUCTORS; TRANSPARENT; DISPLAY; PANEL; LOAD; TFT